2019
DOI: 10.59284/jgpeman97
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting cesarean deliveries with robust time series models in a tertiary care hospital

Abstract: Introduction: Caesarian section rate was 47% at Patan Hospital in 2014 despite the recommendation of keeping it below 15%. This has become a public health problem and it is debated as human right violation of childbearing women. This study aims use robust time series model to forecast caesarian deliveries to keep track of it at the hospital. Method: Univariate time series models were used to forecast 3-year caesarean deliveries at Patan Hospital using 60-month (2010-2014) data. A robust time series model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The increasing or upward trend in CS cases revealed in this study also concurs with the findings of other researchers [6,8,9,17]. Bosson-Amedenu et al [6] study exhibited an increasing or upward trend for CS incidence rate (both within the study period and the forecast period) for all the then ten (10) regions of Ghana, however, that study showed seasonal pattern in CS incidence rate for Eastern, Greater Accra and Ashanti regions respectively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The increasing or upward trend in CS cases revealed in this study also concurs with the findings of other researchers [6,8,9,17]. Bosson-Amedenu et al [6] study exhibited an increasing or upward trend for CS incidence rate (both within the study period and the forecast period) for all the then ten (10) regions of Ghana, however, that study showed seasonal pattern in CS incidence rate for Eastern, Greater Accra and Ashanti regions respectively.…”
Section: Discussionsupporting
confidence: 91%
“…The seasonal pattern for Eastern region peaked in January; Greater Accra peaked in May whereas Ashanti region peaked in both May and October. Pradhan, and Bhandary [8] in their study rather had a decreasing CS rate in their forecast though the study period exhibited increasing CS rate. The forecast of Caesarean section incidences in UCC hospital for the period of August 2021 to July 2026 indicates an increasing trend or an upward movement for the CS mode of childbirth with an expected rate of over 40%.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation